Report of the Task Force on Land and Soil Resources - Planning Commission (Planning Commission, 1972)
This task envisages a scientific utilization of data and maps, that emanate from Tasks I to III for various practical purposes by different user agencies. A review of the present land use, various lacuna in land use, and need for determining land productivity and potentiality have been outlined.
The Steering Group on Natural Resources Surveys Planning Commission
The Steering Group on Natural Resources Surveys Planning Commission